2014
DOI: 10.1017/s0021932013000734
|View full text |Cite
|
Sign up to set email alerts
|

Regional Variations in Infant and Child Mortality in Nigeria: A Multilevel Analysis

Abstract: SummaryThere are substantial regional disparities in under-five mortality in Nigeria, and evidence suggests that both individual- and community-level characteristics have an influence on health outcomes. Using 2008 Nigeria Demographic and Health Survey data, this study (1) examines the effects of individual- and community-level characteristics on infant/child mortality in Nigeria and (2) determines the extent to which characteristics at these levels influence regional variations in infant/child mortality in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
96
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(138 citation statements)
references
References 40 publications
(75 reference statements)
23
96
0
Order By: Relevance
“…Many studies have noted a differential in rural-urban child survival rates in developing as well as in developed countries [36] [37]. The urban mortality advantage in terms of health care facilities and infant and child mortality was observed in India [38] [39]. The finding from our analysis related to rural-urban mortality gap is in agreement with the findings of these studies.…”
Section: Discussionsupporting
confidence: 91%
“…Many studies have noted a differential in rural-urban child survival rates in developing as well as in developed countries [36] [37]. The urban mortality advantage in terms of health care facilities and infant and child mortality was observed in India [38] [39]. The finding from our analysis related to rural-urban mortality gap is in agreement with the findings of these studies.…”
Section: Discussionsupporting
confidence: 91%
“…The childhood mortality differentials according to these variables have been previously described. [16,17] The random component in the multilevel model showed significant intracommunity correlation in the risk of child death. This correlation justified the analytical method used in the present study because children in the same community are exposed to similar circumstances, cultural norms and practices, and thus they would not have been completely independent of one another as far as the underfive death rate was concerned.…”
Section: Discussionmentioning
confidence: 97%
“…[6,15,16] These studies showed that contextual variables such as residence (rural v. urban), community level of education, Background. Although decision-making authority is associated with maternal healthcare utilisation, the evidence on the relative importance of individual-level v. community-level decision-making participation for child survival in sub-Saharan Africa is limited.…”
mentioning
confidence: 99%
“…This finding is consistent with a similar study in Nigeria. [6] The risk of child mortality was significantly reduced for children whose mothers were married. Children who belong to households with family size of five or more people had significantly reduced risk of child mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Numerous studies on the determinants of child mortality have been conducted in LMICs including Nigeria. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Findings of these studies showed…”
Section: Introductionmentioning
confidence: 99%